2015
DOI: 10.1590/s0102-053620150000300003
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de acessos de pimentas do Amazonas

Abstract: Morphological characterization of Amazon pepper accessionsIn Brazil wide variability is found in peppers of Capsicum genus and the Amazon region is an important center of diversity. Information about the diversity in collection is useful, among other aspects, to increase the efficiency of breeding studies of cultivated species. The present study aimed to characterize the morphology and estimate the genetic diversity of 40 Capsicum accessions from Universidade Federal do Amazonas germplasm collection. Morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 11 publications
1
14
0
5
Order By: Relevance
“…Analyzing the duration of the phenological phases, it is observed that there was overlapping of vegetative growth and maturation in approximately 72 days. These results are close to those obtained by Costa et al (2015), when analyzing the growth of 40 accessions of pepper, having observed vegetative growth up to 60 DAT, flowering between 61 to 90 DAT, while the fruiting occurred between 60 to 180 DAT coinciding with the fruit maturation. It is verified that the authors registered vegetative and reproductive phase overlapping in approximately 120 days, a difference of 24 days in relation to the results of this study, which is a result of the difference in the cultivation cycles (112 and 180 days).…”
Section: /7supporting
confidence: 90%
See 1 more Smart Citation
“…Analyzing the duration of the phenological phases, it is observed that there was overlapping of vegetative growth and maturation in approximately 72 days. These results are close to those obtained by Costa et al (2015), when analyzing the growth of 40 accessions of pepper, having observed vegetative growth up to 60 DAT, flowering between 61 to 90 DAT, while the fruiting occurred between 60 to 180 DAT coinciding with the fruit maturation. It is verified that the authors registered vegetative and reproductive phase overlapping in approximately 120 days, a difference of 24 days in relation to the results of this study, which is a result of the difference in the cultivation cycles (112 and 180 days).…”
Section: /7supporting
confidence: 90%
“…Results of this study corroborates with Pedó et al (2013a), since they were close to the maximum height observed by the authors, which was of 780 mm in the Doce cultivar. Costa et al (2015) evaluated the height growth of 40 accessions of peppers (Capsicum spp.) from different provinces of the Amazonas Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, pepper cultivation gives producers more marketing opportunities in various segments, either for fresh consumption or industry (Signorini et al, 2013). The importance of pepper cultivation is directly associated with its consumption, being considered one of the most important species used by family farmers (Costa et al, 2015;Signorini et al, 2013). According to ABCSEM (2016), more than 3,322 kg of pungent and not pungent hot pepper seeds were sold in Brazil in 2011, with an estimate of 2,460 ha planted area.…”
Section: Introductionmentioning
confidence: 99%
“…A agricultura urbana e periurbana (AUP) adquiriu destaque no cenário nacional a partir da década de 1990, afirmando-se como mecanismo de inclusão nos sistemas de crescimento sustentável das pessoas e do ambiente (COSTA, 2015).…”
Section: Introductionunclassified